The role of nitrifier denitrification in the production of nitrous oxide revisited. (August 2018) - Wrage-Mönnig, Nicole; Horn, Marcus A.; Well, Reinhard; Müller, Christoph; Velthof, Gerard; Oenema, Oene
Abstract: Nitrifier denitrification is the reduction of nitrite (NO2 − ) by ammonia-oxidizing bacteria. This process may account for up to 100% of nitrous oxide (N2 O) emissions from ammonium (NH4 + ) in soils and is more significant than classical denitrification under some conditions. Investigations of nitrifier denitrification have expanded in the last decade but many aspects are still not understood. In this review, we revisit our 2001 paper, present a comprehensive summary of current knowledge concerning nitrifier denitrification, and identify the many research needs. Nitrifier denitrification can be distinguished from other routes of N2 O production using isotopic methods: either isotopomer techniques or a combination of 15 N and 18 O tracers. Our understanding of the regulation and conditions favouring nitrifier denitrification has improved over the last decade as a result of adopting molecular and modelling approaches. Environments low in oxygen, and especially those with fluctuating aerobic-anaerobic conditions, promote N2 O production by nitrifier denitrification. Also, large NO2 − concentrations, which often arise following inputs of ammonium or urea, may be linked to changes in aerobicity and high pH and favour nitrifier denitrification. The effects of temperature and carbon contents on nitrifier denitrification are incompletely understood and future research needs include: the study of pathways similar to nitrifier denitrification in archaea and nitrite oxidizers; the effects of interactions among microorganisms and between microorganism and plants; and the regulation and importance of the enzymes involved. A comparison and evaluation of the methods used for differentiating the sources of N2 O is urgently needed. Furthermore, results from studies of freshwater and marine environments as well as wastewater treatment, where nitrifier denitrification is also known as nitrous aerobic denitritation (up to N2 O) or aerobic denitritation (up to N2 ), will further advance our understanding.